PENERAPAN TEKNOLOGI PENGIDERAAN JAUH DI BIDANG PESISIR DAN LAUTAN - Muhammad Zainuddin Lubis; Oktavianto Gustin; Wenang Anurogo; Husnul Kausarian; Kasih Anggraini; Aditya Hanafi (OSEANA, 2017)
APPLICATIONS OF REMOTE SENSING TECHNOLOGY IN COASTAL AND OCEAN Many remote sensing applications are devoted to the coastal and ocean sector. Representative case studies are presented in the special issue “Advances in Remote Sensing of coastal and ocean”. Remote sensing techniques represent a powerful tool for landslide investigation: applications are traditionally sea surface temperature, marine habitat into three main classes, although this subdivision has some limitations and borders are sometimes fuzzy in coastal and ocean. Remote sensing combined with geographic information system (GIS) can be used as a technology tool to obtain information about the object quickly and accurately, including objects in coastal and ocean areas. Remote sensing data on coastal and marine areas specifically for the region in Indonesia have been widely practiced. The use of remote sensing data and GIS in coastal and marine areas can be used to determine sea surface temperature, determination of fish catchment area, and coastline morphological changes by adding other influential parameters. It can also be used to monitor a regional change by using multi-temporal recording data such as disaster monitoring, monitoring of land cover changes in coastal areas etc. Remote sensing data essentially can be used as an alternative technology in obtaining information at a cheaper cost when compared with the conventional way.